Promoting Effective Thinking in ESP teaching - Šliogerienė, Jolita (Acta Paedagogica Vilnensia, 2005)
Annotation. The paper presents some ways of fostering student’s reflective thinking in learning English for specific purposes. It also describes the key aspects of reflective thinking in connection with metacognitive awareness and presents the most widely used techniques in self-assessment and self-management skills, such as evaluation sheets, learning diaries and portfolios which are wide-ranging in ESP learning/teaching context. The article focuses on self-assessment in portfolio use and students’ need to self-evaluate their learning process and emphasizes the increased awareness of learning and teaching styles. Reflective thinking as central to students’ self-evaluation is described as the use of those cognitive skills or strategies that increase the probability of a desirable outcome. Critical thinking is a shift from teaching students’ facts and what the teacher knows to teaching students how to think for themselves.